1989
DOI: 10.1111/j.1744-7348.1989.tb03381.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of three screening techniques for the evaluation of fungicides to control rhizoctonia root rot of wheat

Abstract: Twenty fungicides were screened for their abilities to reduce the saprophytic growth of Rhizoctonia solani on agar and in soil, and t o control root rot of wheat (Triticum aestivum) in pots of soil. Thirteen showed some activity against the in vitro growth of R. solani, the most promising being Sandoz 619F and flutolanil, although none of these reduced saprophytic growth of the fungus in soil. Only benomyl and thiabendazole, which were ineffective on agar and against disease in pots, reduced saprophytic growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The effects of seeding date, seeding depth, seed size and seed treatment have been studied on Rhizoctonia seedling blight of canola (Nuttall 1982;Cotterill et al 1989;Kataria et al 1993;Hwang et al 2014). To our knowledge, however, no data are available on the effects of seeding date, seeding depth, seed size or seed treatment on canola seedling blight caused by F. avenaceum or Pythium spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of seeding date, seeding depth, seed size and seed treatment have been studied on Rhizoctonia seedling blight of canola (Nuttall 1982;Cotterill et al 1989;Kataria et al 1993;Hwang et al 2014). To our knowledge, however, no data are available on the effects of seeding date, seeding depth, seed size or seed treatment on canola seedling blight caused by F. avenaceum or Pythium spp.…”
mentioning
confidence: 99%
“…In Canada, several fungicides have been evaluated for the control of preand post-emergence damping-off of canola caused by R. solani (Cotterill et al 1989;Kataria et al 1993). In western Canada, canola seed treatment fungicides are usually formulated to provide protection against a broad spectrum of fungal pathogens such as Pythium spp., Fusarium spp.…”
mentioning
confidence: 99%
“…The metalaxyl components were utilized to mitigate the confounding effects of Pythium in the soil. Cotterill et al (1989) studied the effect of seed treatment fungicides and reported that cyproconazole almost completely controlled pre-emergence damping-off. However, the treatment did not provide post-emergence control of canola seedling blight, and treatment with carboxin yielded similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Fungicide seed treatments provide an effective means to reduce damage from seedling blight and root rot pathogens (Verma 1996). In Canada, several fungicides have been evaluated to control pre-and post-emergence damping-off canola resulting from infection by R. solani (Cotterill et al 1989;Kataria et al 1993). In western Canada, canola seed treatment fungicides are usually formulated to provide protection against a broad spectrum of fungal pathogens, including Pythium spp., Fusarium spp.…”
mentioning
confidence: 99%